Assessment of Knowledge, Attitude and Practices Regarding Breastfeeding among Mothers Having Children Below 1 Year - Ramandeep Kaur; Manjit Kaur; Jyoti (Institute of Medico-legal Publications Pvt Ltd, 2021)
A study to assess the knowledge, attitude and practice regarding breastfeeding among the mothers having children below 1 year. The objectives of the study are to assess the level of knowledge, attitude and practices regarding breastfeeding in mothers having children 1 year, to find out the relationship between knowledge attitude and practices with selected demographic data/variables and to determine correlation between knowledge, attitude and practices. Quantitative research approach and descriptive research design were used. Convenient sampling technique was used to select the 60 subjects. Permission of data collection was taken from head of the department of paediatrics, GMCH Sec-32 Chandigarh. The data was analyzed by using descriptive and inferential statistics. Results of the studies were presented in the form of figures and tables. The study findings revealed that 83.33% mothers had average knowledge regarding breastfeeding, 13.3% mothers had good knowledge and 3.3% mothers had poor knowledge. The study also shows that 88.3 % mothers had positive attitude and 11.7% mothers had negative attitude regarding breastfeeding. The practices were adequate in 91.7% mothers and 8.3% had inadequate practices of breastfeeding. Among all socio-demographic variables, only occupation and parity has significant relationship with attitude score. Only type of family has significant relationship with practice score. The findings revealed non-significant correlation (r=0.058, p=0.636) between knowledge and attitude, statistically significant positive correlation (r=0.290, p=0.038) between knowledge and practices, non-significant correlation (r=0.110, p=0.396) between attitude and practices. This project was carried out by students of final year of B.Sc.(N) Ashish, Ashu, Balraj, Dency, Gaganjot, Harsimran at GMCH-32.